Lower-limb lean mass asymmetry ranges and their association with jump performance in collegiate athletes - Kramarenko, V.; Oldham, M.; Bernhardt, V.; Strogalev, N.; Jones, B.; Banks, B.; Sabo, D.; Alonso, F.; Nate, J.; Pegueros, K.; Bakcha, O.; Tapia Ochoa, S. (International Journal of Exercise Science Conference Proceedings, 2026)
INTRODUCTION: Lower-limb asymmetries have gained increasing attention due to their potential influence on athlete health and performance. Previous research provides mixed findings on the impact of asymmetries on jump performance. PURPOSE: The purpose of this study was to explore lower-limb asymmetry ranges associated with changes in jump performance in a large, multi-sport cohort of athletes.